2015
DOI: 10.4067/s0717-95022015000100015
|View full text |Cite
|
Sign up to set email alerts
|

Learning Anatomy Through Dissection: Perceptions of a Diverse Medical Student Cohort

Abstract: SUMMARY:The debate on how best to teach anatomy and the central role of cadaveric dissections in medical training remains topical even today. Despite the use of a variety of teaching methodologies e.g. prosected specimens, plastinated specimens, cadaveric dissection and computer-assisted learning, the amount of time dedicated to a full body human dissection programme, its clinical relevance and whether it promotes deeper learning has become a bone of contention in problem-based learning context. The implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
1
20
0
3
Order By: Relevance
“…As well as reinforcing the theoretical aspects of their education, dissection also offers the student the opportunity to gain a better understanding of the human body. Working on a cadaver is undoubtedly a deeply emotional experience, but also one that allows students to develop the competence and coping skills that will be applied later in their professional careers (Marcos et al, ; Elizondo‐Omaña et al, ; Böckers et al, ; Van Wyk and Rennie, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As well as reinforcing the theoretical aspects of their education, dissection also offers the student the opportunity to gain a better understanding of the human body. Working on a cadaver is undoubtedly a deeply emotional experience, but also one that allows students to develop the competence and coping skills that will be applied later in their professional careers (Marcos et al, ; Elizondo‐Omaña et al, ; Böckers et al, ; Van Wyk and Rennie, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large volume of literature is available which elaborates on the ideal methods of teaching/learning anatomy, however, very few focus on the students' perceptions regarding the anatomy curriculum. Researchers have observed that students have strong opinions regarding anatomy education and it has been suggested that these inputs could have a considerable impact on curriculum development (Van Wyk and Rennie, 2015). Some studies have critically evaluated the perceptions of the students regarding the factors that affect their learning in anatomy (Drake et al, 2009;Holla et al, 2009;Cho and Hwang, 2013).…”
Section: Perceptions Of Medical Students Regarding Their Experience Wmentioning
confidence: 99%
“…They are of the opinion that undertaking dissection activated their senses of sight and touch, which in turn increased their understanding of anatomy. Such appreciation of visual and tactile stimuli is essential when students, as future practicing doctors are called upon to examine patients (Van Wyk and Rennie, 2015). Learning of anatomy by dissection enables students to connect and correlate knowledge, which helps them to gain conceptual insights, which is necessary for deep and satisfying learning (Entwistle and Tait, 1995).…”
Section: Positive Outlook Of Students Towards Dissectionmentioning
confidence: 99%
See 2 more Smart Citations